PENGARUH AKTIVITAS, MINAT DAN OPINI TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA SALON CHIQUITA DI KOTA PALU - LESTARI, WIDYA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
The purpose of the research is to find out the influence of activity, interest, and opinion on consumer decision in using Chiquita Salon in Palu City. There are 4 variables that used in this research; activity (X1), interest (X2), opinion (X3), and decision of the consumer (Y). Method of study is descriptive causal with a total sample of 60 respondents, who were selected by purposive sampling. Tool of analysis is multiple linear regressions with Software SPPS 17. The result finds that activity (X1), interest (X2), and opinion (X3) simultaneously influence the decision of the consumer in using Chiquita Salon in Palu City, with the level of significance of 0.000 < ? 0.05. Furthermore, activity (X1) with the t-sig. value of 0.042; interest (X2) has the t-sig. value of 0.022; opinion (X3) has the t-sig. value of 0.001. These values are < 0.05, which means that each variable partially influences the decision of the consumer in using Chiquita Salon in Palu City.